Evaluation of Midterm Clinical and Radiographic Outcomes of Arthroscopically Repaired Vertical Longitudinal and Bucket-Handle Lateral Meniscal Tears. Issue 5 (9th May 2019) - Uzun, Erdal; Misir, Abdulhamit; Kizkapan, Turan Bilge; Ozcamdalli, Mustafa; Akkurt, Soner; Guney, Ahmet
Background: Lateral meniscal tears in the stable knee are rare. There are few comparative studies evaluating functional and radiological outcomes of vertical longitudinal and bucket-handle lateral meniscal tears. Purpose: To evaluate the midterm clinical and radiological outcomes of arthroscopically repaired traumatic vertical longitudinal and bucket-handle lateral meniscal tears. Study Design: Case series; Level of evidence, 4. Methods: A total of 43 full-thickness lateral meniscal repairs, including 22 (51.2%) for vertical longitudinal tears and 21 (48.8%) for bucket-handle tears, were evaluated. A clinical assessment was performed according to the Barrett criteria, and patient outcomes were measured with the Lysholm knee score, Tegner activity scale, and overall satisfaction scale. Magnetic resonance imaging was used as the radiological re-examination method preoperatively and at final follow-up. A subgroup analysis examining isolated repair versus repair with concurrent anterior cruciate ligament (ACL) reconstruction was performed. Results: The mean follow-up period was 63.2 months (range, 24-86 months). Based on clinical and radiological outcomes, 38 of the 43 repairs (88.3%) were successful, and the remaining 5 (11.6%) cases were considered to be failures. Overall, the combined results for both groups demonstrated an improvement in the Lysholm score, Tegner score, and patient satisfaction. There was no significant difference in the postoperative Lysholm score (91.4 vs 87.0, respectively; P = .223), Tegner score (5.4 vs 5.5, respectively; P = .872), or patient satisfaction (7.2 vs 7.4, respectively; P = .624) between bucket-handle repair and vertical longitudinal repair. The subgroup analysis demonstrated no difference in outcome scores for isolated repair versus repair with concurrent ACL reconstruction. Smoking was identified as a risk factor for repair failure. Conclusion: Comparable clinical and radiological outcomes were obtained after vertical longitudinal and bucket-handle lateral meniscal repairs using the all-inside or hybrid suture technique with different suture configurations, regardless of whether ACL reconstruction was performed. Smoking was identified as a risk factor for failure.